Dampak Kompetensi Kultural Pada Efektivitas Bimbingan dan Konseling Multibudaya di Universitas Muhammadiyah Makassar - Ratna Wulandari; Alamsyah Alamsyah; Evi Faura Lutfia (JBKPI: Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
Abstrac:College today is becoming an increasingly culturally diverse environment with students coming from a variety of ethnic and cultural backgrounds. In this context, it is important for higher education institutions to provide effective guidance and counseling services to support students in dealing with their academic and personal challenges. This study aims to investigate the impact of cultural competence on the effectiveness of guidance and counseling in tertiary institutions. By collecting qualitative data through interviews with counselors at the Muhammadiyah University of Makassar, this research explores how the cultural competence of counselors contributes to the results achieved in guidance and counseling. The results of the study show that the cultural competence of the counselor has a significant impact on the effectiveness of guidance and counseling. Counselors who have a deep understanding of student culture are able to build better connections with them, creating strong bonds and building trust. In addition, a good understanding of the cultural context of students allows counselors to provide more relevant and effective interventions.